Caracterização funcional e bioquímica do fator de transcrição rlmA e da interação de PkcA e Hsp90 no fungo Aspergillus fumigatus - Rocha, Marina Campos (Universidade Federal de São Carlos, 2017)
Aspergillus fumigatus is an opportunistic human pathogen that causes systemic infections, including invasive pulmonary aspergillosis in immunocompromised individuals. Survival of this fungus is highly dependent on the cell wall organization and function of its structural components. Cell wall integrity pathway (CWIP) is the primary signaling cascade that controls de novo synthesis of the cell wall. In Sacharomyces cerevisiae, this event depends on the RLM1 transcription factor that contains the MADS-box domain. In this work, we investigated the function of RlmARLM1 in the CWIP of A. fumigatus. We show that the ΔrlmA strain presents an altered cell wall composition, besides defects related to vegetative growth and cell wall integrity in the presence of cell wall stressors agents. Genetic assays indicated that rlmA is positioned downstream of pkcA and mpkA genes in CWIP, and, as a consequence, the loss of rlmA function results in alteration of genes expression of the encoding cell wall related proteins. The transcription factor RlmA positively regulates the phosphorylation of MpkA, which is induced in both protein and transcriptional levels during cell wall stress. rlmA is also involved in tolerance to oxidative stress, whereas the main genes that regulate tolerance to reactive oxygen species had their expression reduced in the ΔrlmA mutant. In addition, ΔrlmA strain presents attenuated virulence in a murine model of invasive pulmonary aspergillosis and induced increased secretion of TNF-α. There was a higher rate of conidia phagocytosis of the mutant ΔrlmA in comparison to the wild type. The ΔrlmA mutant exhibits reduced asexual sporulation, and regulates transcription of the major transcription factors involved in conidiogenesis in Aspergillus ssp., i.e. brlA and abaA. RlmA is also important in the production of secondary metabolites, including gliotoxin and fumiquinazoline (Fq) C, and positively regulates the transcription of the genes cluster responsible for Fq biosynthesis. A biological characterization showed that activity of FqC increase the production of the inflammatory cytokines TNF-α, IL-6, and pore formation in the plasma membrane, suggesting that this is a defense mechanism against other microorganisms or soil predators. Additionally, the role of the second transcription factor (SebA) in the production of FqC in A. fumigatus was reported. We have shown that maintenance of cell wall integrity is associated with thermotolerance in A. fumigatus, and the Hsp90, one of the main chaperone involved in the heat shock response, physically interacts with PkcA, MpkA, and RlmA. Furthermore, partial or total loss of function of these genes results in altered expression of the principal genes related to heat shock response in A. fumigatus. Additionally, the proteins MpkA and Hsp90 had their structure partially characterized. Overall results suggest that RlmA works as a transcription factor associated with the A. fumigatus CWIP acting downstream of the PkcA-MpkA signaling and regulating the response to several stresses caused to the fungal cell which emphasizes the importance of this pathway in the virulence and pathogenicity of this fungus.
Functional and biochemical characterization of the rlmA transcription factor and the interaction of PkcA and Hsp90 in the fungus Aspergillus fumigatus
Keywords: Parede celular; Metabólitos secundários; Aspergillus fumigatus; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::MICOLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::BIOQUIMICA; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA